On possibility of short-living positron-emitting nuclides production using electron accelerator for medical diagnostics - Zadvorny, A.S. (Вопросы атомной науки и техники, 2011)
Comparison is made of technologies of radiopharmaceuticals (RPC) production that are labeled with positron-emitting nuclides using a cyclotron and an electron accelerator (EA). It is shown that specific activities of RPC produced on EA are sufficient for the g-camera and PET diagnostics. Проведено порівняння технологій отримання радіофармпрепаратів (РФП), мічених позитрон-випромінюючими нуклідами, які отримуються на циклотроні та електронному прискорювачі (ЕП). Показано, що питомі активності РФП, які отримані на ЕП, достатні для діагностики на g-камері та для ПЕТ-досліджень. Проведено сравнение технологий получения радиофармпрепаратов (РФП), меченных позитрон-излучающими нуклидами, получаемых на циклотроне и электронном ускорителе (ЭУ). Показано, что удельные активности РФП, полученные на ЭУ, достаточны для диагностики на g-камере и для ПЭТ-исследований.